The effects of fibre volume fraction of composite plate - Chan, Wai Theng (2007)
Composite materials especially glass fibre reinforced plastics (GFRP) are being widely used in many industry nowadays due to its special mechanical properties and light weight. The performance of composite materials is often controlled by fibre volume fraction, V1. Hence, the main objective of this study is to investigate the effect of V1 onto the mechanical properties of composite plate. The fibre used is chopped strand mat (CSM) type E-glass fibre where the matrix used is based on unsaturated polyester resin. The composite plates were prepared by hand lay-up technique. Rule of mixture (ROM) and modified rule of mixture (MROM)were used to predict the performance of the composite plates. Tensile test according to ASTM D 3039 was carried out to obtain ultimate strength and modulus of elasticity of the composite plate with different V1. Three different composite systems were tested in this study. The actual Vj ofthe composite plates were justified by burn out test (SIRIM MS 1390:1995). MROM was found had better validity than ROM to be used to estimate the mechanical properties of specimens after compared with experimental results. The experimental results show that the mechanical properties were improved when V1 is increased. Thus, the influence of fibre volume fraction on the mechanical properties of CSM E-glass fibre/polyester composites has been evaluated.